The perception of swear words by French learners of English: an experiment involving electrodermal activity - Anastasija Rastovic; Maud Pélissier; Emmanuel Ferragne (Anglophonia)
Hearing swear words or taboo words causes us discomfort. Research suggests that emotional responses caused by such words are stronger when the words are spoken in the listener’s first language (L1), rather than their second language (L2). We attempt to replicate these findings with a perceptual experiment. French learners of English were asked to listen to English and French swear words while their electrodermal activity (EDA) was monitored. Emotionally-neutral words were also included as baseline. EDA records small fluctuations in skin conductance caused by variations in the activity of sweat glands. Such variations are known to be correlated to the emotional state of the listener and reflect levels of stress or arousal in particular. We found a Word type ✕ Language interaction, which shows strong emotional reactions to swear words limited to the listener’s first language. This supports the claims that the L1 and L2 may be embodied differently, with the L2 being processed only semantically but not affectively. The role of different factors on L2 emotionality is discussed.